Microstructural characteristics of turbot (Scophthalmus maximus) muscle: effect of salting and processing. Issue 1 (1st January 2018) - Li, De-Yang; Huang, Ying; Wang, Ke-Xin; Dong, Xiu-Ping; Yu, Da; Ge, Li-Hong; Zhou, Da-Yong; Yu, Chen-Xu
ABSTRACT: The effect of salt concentration on the processing and characteristics of turbot muscle was investigated in this study. The turbot muscle samples were salted with 1%, 5%, 10%, 15%, or 20% w/w salt at 4°C for 3 h. Low-field nuclear magnetic resonance was utilized to characterize water distribution and water holding capacity in the samples. Nuclear magnetic resonance transverse ( T 2 ) relaxation identified three water components ( T 21, T 22, and T 23 ) which all exhibited characteristics correlated with water holding capacity. Textural analysis indicated that hardness and elasticity increased with increasing salt concentration. Histological imaging showed that with the increase of salt concentration, the muscle fiber diameter and area increased first and then decreased. The porosity of salted samples was higher than that of fresh ones. It was shown that salting at lower salt concentrations would lead to partial degradation of the fibrin in the tissue samples and the swelling of proteins. In treated samples, 5% w/w salt was shown to produce the best results. This study provides theoretical basis for the development of salted turbot meat products.